Interval Waktu Pemberian Nutrisi Terhadap Produksi Tanaman Selada Hijau (Lactuca sativa L) Varietas New Grand Rapid Pada Sistem Aeroponik - Rommy Andhika Laksono (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
Lettuce production in Indonesia is still low, so the demand for lettuce cannot be fulfilled. Lettuce production can be increased with aeroponic systems because aeroponic systems can be carried out in various places including urban areas and areas that have high land conversion.. The purpose of this study was to study and obtain the best time intervals of nutrition in lettuce New Grand Rapid varieties with the Aeroponic System. This research was conducted in a screen house in Leuwimalang Village, Cisarua, Bogor Regency, West Java from August to November 2019. The study used a single factor randomized block design (RBD), consisting of 6 treatments with 5 replications, so that there were 30 experimental units. t1 = 30 seconds (on): 5 minutes (off)]; [t2 = 30 seconds (on): 10 minutes (off)]; [t3 = 30 seconds (on): 15 minutes (off)]; [t4 = 30 seconds (on): 20 minutes (off)]; [t5 = 30 seconds (on): 25 minutes (off)]; [t6 = (Non Stop)]. The provision of nutrition with different time intervals in the aerophonic system gave different effects on the average plant height, number of leaves, stem diameter, leaf area and fresh weight per lettuce plant, and continuous nutrition treatment (Non Stop) gave the results of fresh weight the highest was 203.10 g